Vaccine development to prevent Staphylococcus aureus surgical‐site infections. Issue 2 (25th January 2017) - Mohamed, N.; Wang, M. Y.; Le Huec, J.‐C.; Liljenqvist, U.; Scully, I. L.; Baber, J.; Begier, E.; Jansen, K. U.; Gurtman, A.; Anderson, A. S.
Abstract: Background: Staphylococcus aureus surgical‐site infections (SSIs) are a major cause of poor health outcomes, including mortality, across surgical specialties. Despite current advances as a result of preventive interventions, the disease burden of S. aureus SSI remains high, and increasing antibiotic resistance continues to be a concern. Prophylactic S. aureus vaccines may represent an opportunity to prevent SSI. Methods: A review of SSI pathophysiology was undertaken in the context of evaluating new approaches to developing a prophylactic vaccine to prevent S. aureus SSI. Results: A prophylactic vaccine ideally would provide protective immunity at the time of the surgical incision to prevent initiation and progression of infection. Although the pathogenicity of S. aureus is attributed to many virulence factors, previous attempts to develop S. aureus vaccines targeted only a single virulence mechanism. The field has now moved towards multiple‐antigen vaccine strategies, and promising results have been observed in early‐phase clinical studies that supported the recent initiation of an efficacy trial to prevent SSI. Conclusion: There is an unmet medical need for novel S. aureus SSI prevention measures. Advances in understanding of S. aureus SSI pathophysiology could lead to the development of effective and safe prophylactic multiple‐antigen vaccines to prevent S. aureus SSI. Abstract : Optimistic future